Patterns of, and Factors Associated With, Illicit Pharmaceutical Opioid Analgesic Use in a Prospective Cohort of People Who Inject Drugs in Melbourne, Australia - Horyniak, P.; Agius, P.; Degenhardt, L.; Reddel, S.; Higgs, Peter; Aitken, C.; Stoove, M.; Dietze, P. (Taylor & Francis Inc., 2015)
Background: People who inject drugs (PWID) are a key population engaging in pharmaceutical opioid analgesic (PO) use, yet little is known about patterns of illicit PO use among this group. Objectives: The aims of this research were to measure the prevalence and frequency of lifetime and past-month illicit PO use and injection in a sample of regular PWID, to examine patterns of past-month illicit PO use within individuals over time, and to identify factors independently associated with past-month illicit PO use. Methods: Data were drawn from a prospective cohort study of regular PWID (N = 666) in Melbourne, Australia. Data from five waves of annual data collection (including baseline) were analyzed descriptively and using generalized estimating equations (GEE). Results: At baseline, 59% of participants reported lifetime illicit PO use and 20% reported past-month use, predominantly through injecting. Most illicit PO users at baseline transitioned to nonuse of illicit POs across the study period. In multivariable GEE analysis, factors associated with past-month illicit PO use included past-year arrest [adjusted odds ratio (AOR): 1.39], opioids other than heroin as drug of choice (AOR: 5.14), experiencing poorer physical health (AOR: 0.98) and a range of other drug use variables. Conclusions: We found little evidence of ongoing illicit PO use among those followed up, with illicit PO use linked to polydrug use more broadly. Nonetheless, trends in illicit PO use among PWID should continue to be monitored and harm reduction interventions implemented to reduce the associated public health risks.